Evidence implicating descending fibers in self-stimulation of the medial forebrain bundle - Bielajew, C (J Neurosci, 1986)
The role of ascending and descending fibers in self-stimulation of the lateral hypothalamus and ventral tegmental area in the rat was assessed by noting whether anodal hyperpolarization of one of these sites could reduce the rewarding effect of stimulating the other site. Strength- duration curves were obtained by psychophysical means, with one of the depth electrodes serving as the cathode and the other as the anode. It was anticipated that at long pulse durations, conduction in some of the fibers stimulated at the cathode would be blocked at the anode. At shorter durations, the anodal hyperpolarization should have dissipated before the arrival of the action potentials triggered by the cathode. Thus, the predicted effect of the block was to bend the strength- duration curves obtained with two depth electrodes upward at long pulse durations, provided that the anode lay between the cathode and the efferent stages of the pathway responsible for the rewarding effect. To control for possible differences in the density of the reward substrate in the lateral hypothalamic and ventral tegmental areas, the strength- duration curves obtained with a given cathode and a depth anode were compared to curves obtained with the same cathode but with an anode consisting of a set of skull screws. It was expected that the concentrated current entering from the depth anode would much more effectively block conduction in the medial forebrain bundle than the diffuse current entering from the large, distant skull screws. The predicted change in the shape of the strength-duration curves was observed only when the ventral tegmental electrode served as the anode and the lateral hypothalamic electrode as the cathode. This is consistent with the notion that in at least some of the neurons responsible for the rewarding effect, action potentials elicited by the lateral hypothalamic electrode had to pass through the ventral tegmental area in order to reach the efferent stages of the reward pathway. In the simplest anatomical arrangement consonant with this view, the somata of these cells lie in the forebrain and give rise to descending axons. As a test of the hypothesis that anodal block was responsible for changing the shape of the strength-duration curve obtained with the ventral tegmental anode, a psychophysical version of the collision test was used to determine whether the tips of the lateral hypothalamic and ventral tegmental electrodes were indeed linked by a common set of reward-related fibers.(ABSTRACT TRUNCATED AT 400 WORDS)